Comparison of Interrelationship with Site Occupancy, Population Structure and Foraging Ecology of Lesser Whistling Duck (Dendrocygna javanica) Among 10 Wetland Habitats of Paya Indah Wetlands, Peninsular Malaysia - Zakaria, Mohamed; Martins, Onwuka C; Rajpar, Muhammad Nawaz; Olaniyi, Oluwatobi E (Edelweiss Applied Science and Technology, 2020)
Protecting ecosystems in the vicinity of rapidly urbanizing areas requires continuous monitoring and assessment. Currently, the extent of occurrence <20,000 km2 combined of Lesser Whistling Duck (LWD) is declining or fluctuating in range size, habitat extent/quality and population size. It is mostly found in either small number or small fragmented locations due to limited source of food variety. Hence, the study aimed to evaluate the interrelationship among site occupancy, population structure and foraging ecology of LWD (Dendrocygna javanica) among 10 wetland habitats in a Paya Indah Wetland (PIW), Peninsular Malaysia. Population analysis indicated that PIW harbored LWD density of 4.66 ± 1.12 birds/ha and relative abundance of 1,234 bird individuals. The highest naïve occupancy (NO=0.80), occupancy (Ψ=0.80 ± 0.18) and detection probability (P=0.98 ± 0.01) was detected for Belibis habitat and the lowest occupancy (Ψ=0.31 ± 0.04) in Kemoning habitat. LWD foraged on vegetation predominantly aquatic plants and as well as small vertebrates. The Akaike Information Criteria indicated that, the LWD had significant relationships with occupancy models (R2=0.93) and positive/strong correlationship with food varieties (R2=0.95). The findings indicated that Belibis wetland habitat harbored the highest LWD in terms of relative abundance and density than the other 10 wetland habitats. This study concludes that the interrelationship of site occupancy, density, and foraging ecology of LWD varied among different habitats.